Genetic behavior for seed yield and yield components in sesame (Sesamum indicum L.) under normal irrigation and water stress conditions - El- Latif Kamel Ibrahim, Suzan Abd (2021)
Six divergent genotypes of sesame (Sesamum indicum L.) were crossed using a half diallel excluding reciprocal crosses, to estimate heterosis, combining ability and nature of gene action for studied traits under two irrigation regimes. The two irrigation regimes were normal irrigation conditions with amount of applied water 5952.38 m3/ha and water stress conditions with amount of applied water 2976.19 m3/ha at Etay-El-Baroud Agricultural Research Station, Behaira governorate, Agricultural Research Center, Egypt during 2019 summer season. A randomized complete block design with three replications was used for each irrigation regimes. The variation of genotypes and their components from parents, crosses and parents versus crosses were highly significant for all studied traits under both irrigation regimes and their interactions with irrigation. Variation attributable to general and specific combining ability was highly significant for seed yield and yield components under both irrigation regimes. The parents L92 and L110 were the best combiners for seed weight per plant and most of its components under both irrigation regimes. The best F1 cross combination was L92 × L110 in specific combining ability and heterotic effects over mid- and better-parents under both irrigation regimes for seed weight per plant and most of its attributes. The preponderance of additive gene action in the inheritance of most studied traits was observed, that further confirmed by its significance and the value of average degree of dominance exceeding the unity. Narrow-sense heritability varied from 0.19 for number of branches per plant to 0.47 for 1000 seed weight under normal irrigation, whereas, under water stress conditions, it ranged from 0.14 for number of branches per plant to 0.42 for fruiting zone length. Parents L95 and L93 under normal irrigation and L93 and L110 under water stress conditions carried mostly genes with dominant effects for seed weight per plant, in contrary, L92 and L110 under normal irrigation and L92 and L12 under water stress conditions carried mostly recessive alleles for seed weight per plant. Hence, the results will be used to develop a sesame breeding scheme at Etay-El-Baroud Agricultural Research Station.